Exploring Metaphors in Ariana Grande’s Album Eternal Sunshine: A Stylistic Analysis - Kewa, Erwina; Prafitri, Wilma (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
This research analyzed conceptual metaphors in the song lyrics of selected songs in Ariana Grande's Eternal Sunshine album, using the theory of conceptual metaphors by Lakoff and Johnson (1980) and with the stylistics approach. The research results showed that there were twelve song lyrics containing conceptual metaphors, which were categorized into two types: structural metaphors and ontological metaphors. Structural metaphors worked by connecting a concrete source domain that usually comes from everyday experiences to an abstract target domain such as ideas, feelings, or experiences that have no physical attributes. These structural metaphors provide a framework for understanding emotions and relationships through concepts of everyday experience. Meanwhile, ontological metaphors conceptualized abstract experiences such as activities, ideas, and emotions as something concrete that has a physical entity The stylistic analysis in this research highlighted the use of diction that reinforces the perceived effectiveness of this metaphor and strengthens the emotional resonance for the listener.